Marsūm al-Dawlah al-Indūnīsīyā fī Siyāq al-‘Alāqāt bayn al-Fi’āt al-Dīnīyah - Subhan, Arief (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2009)
This article discusses state regulations related to religious defamation and religious freedom, which are indeed controversial. Some people understand them as part of a larger e?ort to create harmonious and peaceful religious life, while others comprehend them as intervention and a violation of the freedom of religion. The latter groups proposed a judicial review to Law No 1/PNPS/1965. Although the Constitutional Court of Indonesia rejected it, at least it explicates the di?erences in society's views on how far the state is authorized to regulate religious life. The Indonesian Constitution formally acknowledges that freedom of religion is an integral part of civic live.DOI: 10.15408/sdi.v16i3.477